2014
DOI: 10.1186/2193-9020-3-12
|View full text |Cite
|
Sign up to set email alerts
|

Displacement and education of the next generation: evidence from Bosnia and Herzegovina

Abstract: In this paper, I study the effect of displacement (in the sense of forced migration) of parents during a violent conflict on investment in their childrens' education years later. Using the ethnic division during the Bosnian War as a natural experiment, I plausibly identify exogenously displaced households and compare them to households who did not have to move because of the war. Displaced parents spend between 20 and 30% less on the education of their children in primary and secondary school. The result also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 27 publications
(31 reference statements)
1
17
0
Order By: Relevance
“…Therefore using post-displacement income and labour market variables as controls would qualify as using bad controls (Angrist and Pischke, 2008). As education is affected by displacement (Eder, 2014), we circumvent this problem by excluding individuals who were younger than 25 years at the beginning of the war in 1991. We do not include the present county of residence in the estimation as 88.5% of displaced individuals have the same county of residence as before the war.…”
Section: Empirical Strategymentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore using post-displacement income and labour market variables as controls would qualify as using bad controls (Angrist and Pischke, 2008). As education is affected by displacement (Eder, 2014), we circumvent this problem by excluding individuals who were younger than 25 years at the beginning of the war in 1991. We do not include the present county of residence in the estimation as 88.5% of displaced individuals have the same county of residence as before the war.…”
Section: Empirical Strategymentioning
confidence: 99%
“…(For example, Kondylis (), analysing post‐war Bosnia, showed that displaced males are more likely to be unemployed, whereas displaced females are more likely to drop out of the labour force. Eder (), also using post‐war Bosnia, showed that displaced individuals invest less in their children's education. Bauer et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some scholars have focused on analysing outcomes in refugee camps (Lehrer, 2010;Bozzoli et al, 2015;Crea et al, 2015). Other researchers have focused on the impact of forced migration on the welfare of the migrants in the short and medium terms (Ibáñez and Vélez, 2008;Kondylis, 2010;Ibáñez and Moya, 2010;Fiala, 2012;Justino and Verwimp, 2013;Eder, 2014;, as well as in the long-run (Serc, 2009;Falck et al, 2011;Bauer et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Within this field of study, displacement is acknowledged as a clear channel through which war may have an impact on human capital formation (Justino, 2011). Still, only recently has there been any scholarly work on the effects of displacement in particular, in contrast to war in general (Fiala, 2009;Fiala, 2012;Eder, 2013;Oyelere & Wharton, 2013;Verwimp & Van Bavel, 2013). It is within this still relatively unexplored space that this study aims to make a contribution, using a unique dataset for the (post-) conflict context of Afghanistan.…”
Section: Discussionmentioning
confidence: 99%